Determinants of job stress among non-managerial restaurant employees in Klang Valley, Malaysia - Ghazali, Hazrina; Amran, Farah Wahida; Mohamad, Siti Fatimah (Human Resource Management Academic Research Society, 2020)
Despite positive growth of restaurant industry in Malaysia but on the other side of coin, this industry always associated with having low pay, long working hours, lack of benefits, hard work, physically exhausting, and underappreciated thus increasing job stress among employees. The job-related stress is a growing concern among the restaurant operators as it has a significant impact on the performance and productivity of employees. Additionally, excessive and unmanageable stress can be damaging to employees’ health as it affects their mental and physical wellbeing. Therefore, the aim of this study was to identify possible determinants and its influence towards job stress at workplace. The primary data of this study was derived from quantitative method, strictly to Malaysian non-managerial employees only and were distributed to 700 employees who were currently working in casual dining restaurants in Klang Valley area. After screening and data checking, a total of 487 self-completed questionnaires were usable for analysis with 69.6% of response rate. A multiple regression was run to predict job stress and three variables were used that are work environment, workload, and job autonomy. Results found that work environment and workload were statistically significantly predictor of job stress with F (4, 483) = 28.131, p < .0005, R² = .149. These two variables added statistically significantly to the prediction, p < .05 and will be discussed further in this paper. Findings obtained in this study could suggest to owners and restaurant operators to highlight factor that could contribute to job stress and strategize proactive measures to minimize stress and ultimately retain their employees in the industry.